Studies on Synthesis of Some Acid Dyes and Their Application on Various Fibres - Patel, R.B.; Patel, Nilesh; Patel, S.K.; Patel, K.C. (Asian Journal of Chemistry, 2010)
Various acid dyes have been prepared by coupling diazotised 4,4' -methylene- bis-anthranilic acid with various coupling components and their dyeing performance on viscose rayon, wool and silk fibres has been assessed. An the dyes gave a wide range of red to violet shades with very good depth and levelness on each fibre. The purity of all dyes has been checked by thin layer chromatography. The IR spectra showed all characteristic bands and a representative dye PMR spectra showed all the signals. The percentage dye-bath exhaustion and fixation on different fibres was reasonably good and acceptable. The dyed fibres showed fair to exceIlent fastness to light, washing and rubbing.